Genetic and biochemical characterization of staphylococci occurring in Novosibirsk, Russia - Y. N. Kozlova; N. V. Fomenko; V. V. Morozova; I. V. Saranina; A. Yu. Tikunov; D. A. Ganichev; A. G. Samokhin; V. V. Pavlov; O. M. Rozhnova; I. A. Bondar’; E. V. Zenkova; V. V. Nimaev; et al. (Вавиловский журнал генетики и селекции)
Staphylococci are capable of penetrating many human tissues and organs, causing superficial and deep purulent infections, respiratory and urinary tract infections, food poisoning and intoxication. Last years, coagulasenegative staphylococci were the cause of infection in many cases. Infectious agents, namely Staphylococcus epidermidis, Staphylococcus haemolyticus, and Staphylococcus hominis, were detected more often as nosocomial infections. A particular danger of these infections is a high virulence and  pathogenicity of bacterial strains and their resistance to various anti biotics. Methicillinresistant staphylococci are especially difficult to treat. The correct identification of staphylococci and their sensitivity to antibiotics are important for clinical diagnosis and appointment of adequate drug therapy. Rapid and accurate identification of Staphylococcus species and detection of their sensitivity to antibiotics is quite important. The aim of this study was to study staphylococci isolated in Novosibirsk from human, animal and environmental samples. A collection of 100 staphylococcus strains was analyzed. Staphylococcus species were identified by sequencing the 16S rRNA gene. Eleven staphylococcus species were identified. Among the strains obtained from hospitalized patients, Staphylococcus aure us dominated (79.1 %), Staphylococcus  epidermidis amounted to about 12.5 %. However, S. aureus and S. epi dermidis strains were isolated in an approximately equal proportion from communityassociated samples. Identification of coagulase positive strains was performed using a standard biochemical method and by realtime PCR of the coa gene. 100 % coincidence between the presence of the gene and coagulase activity for S. aureus strains was recorded, which suggests that detection of the coa gene can be used as a correct method for S. aure us identification. A high coincidence rate (99 %) was reveal ed between the phenotypic resistance to oxacillin and the presence of the staphylococcal mecA gene. The study of staphylococci for the presence of the mecA gene can be considered as an alternative to the phenotypical method for identification of methicillinresistant strains of staphylococci.